Analisis Penyelesaian Pembiayaan Murabahah Bermasalah Menurut Fatwa DSN MUI No.17/DSN-MUI/IX/2000 dan No. 43/DSN-MUI/VIII/2004 (Studi Kasus di BMT La Tansa Ponorogo) - Zulfatus Sa'diah; Annas Syams Rizal Fahmi; Devid Frastiawan Amir Sup (Journal of Islamic Banking, 2021)
Non-performing financing, namely high Non-Performing Financing is certainly an important problem for Islamic banking, as well as in the Baitul Mal Wa Tamwil KJKS (Islamic Financial Services Cooperative). From the landing side, until now the only financing product at BMT La Tansa Ponorogo is Murabahah. From the system in murabahah itself, it uses the principle of musawamah. The process of negotiating (bargaining) on goods and prices is carried out between the BMT La Tansa Ponorogo and candidate of financing customers. In its journey, BMT La Tansa experienced a problem, namely the non-performing financing ratio which was still high. The methods used in collecting this data are observation, interviews, and documentation.This research is a field research which then analyzed using the DSN-MUI fatwa. The results obtained, that in the settlement of problematic murabahah financing, BMT La Tansa Ponorogo has several stages. Provide warning letters (SP) up to 3 times, confiscation of collateral, rescheduling. Where used in this sanction is mandatory infaq, which is the mandatory infaq amount of Rp. 1,000, - per day (during the late period) and it is already there and written at the beginning of the contract (agreement). While, in terms of ta'wid, BMT La Tansa does not apply ta'wid on non-performing financing made by customers. However, if it is at the final stage that you cannot fulfill the installment obligation, then the purchased item (collateral) is sold to cover the customer's shortage of installments.